Transition metal-based catalysts derived from MOF and COF for efficient electro- and photo-catalytic CO2 reduction - Wang, Haojing (Nanyang Technological University, 2022)
The environmental impact due to the continuous accumulation of greenhouse gases, especially carbon dioxide (CO2), in the atmosphere has caused increasing concern since the end of the last century. The rapid increase of the CO2 concentration is due to a large amount of CO2 released from industry and daily anthropogenic activities where the combustion of fossil fuels becomes the main source of CO2 emission. The induced global environmental problems such as climate change, ocean acidification, and rising sea levels have to be alleviated by developing feasible and sustainable strategies to reduce CO2 emissions. Carbon capture and utilization (CCU) is an emergent method to convert CO2 to value-added chemicals or fuels, which can be recycled and utilized for industrial synthesis. By using renewable energy as the driving force, electrochemical and photochemical CO2 reduction are two attractive methods to achieve CO2 conversion in a sustainable way. However, the slow kinetics of CO2 reduction reaction ascribed to thermodynamically stable properties of CO2 molecules requires efficient catalysts to promote the electro- and photo-catalytic CO2 conversion. Although noble metal-based electrocatalysts and photocatalysts have been widely studied for CO2 reduction for a few decades, the limited resource of noble metals and high cost hinder their large-scale utilization. Therefore, earth-abundant transition metal-containing catalysts for electro- and photo-catalytic CO2 reduction reactions become promising alternatives that have been paid significant attention to in recent years. At the same time, reticular materials with high surface area and tunable coordination, such as metal-organic frameworks (MOFs) and covalent-organic frameworks (COFs), have been investigated to a great extent as ideal support materials or precursors to disperse active metal sites for various catalytic applications. In the past decade, great advances have been achieved in developing various transition metal-based catalysts derived from MOFs and COFs for electrochemical and photochemical CO2 reduction. However, there are still challenging barriers to be solved for both electroreduction and photoreduction of CO2. For electrocatalytic CO2 reduction, low overpotentials, high selectivity for the target product, and long-term durability are three requirements for ideal electrocatalysts that are difficult to be satisfied simultaneously. For photocatalytic CO2 reduction, insufficient light absorption, recombination of charge carriers, and the lack of efficient active sites for CO2 reduction require more efforts to be made for photocatalysts design. There are still great opportunities in harnessing the rich chemical functionality and coordination environment of MOFs and COFs to develop high-performance catalysts. Therefore, the objective of this thesis is to construct rational strategies to derive more efficient and selective electrocatalysts and photocatalysts with earth-abundant transition metal active sites from MOF and COF materials. Chapters 1 and Chapter 2 provide an overview of the background information and literature review about electro- and photo-catalytic CO2 reduction and some advanced catalysts reported in this research field. Chapters 3, 4, and 5 present three different catalysts which were derived from MOFs or COFs with dispersed transition metal active sites for electrochemical or photochemical CO2 reduction. In Chapter 3, an N-rich MOF was chosen as the precursor to derive active Ni-Nx moieties on multilayer graphene. The coordination between inorganic Ni species and organic ligands inside MOFs could be tuned by introducing -NH2 groups into the framework. More N dopants on MOF-derived carbon materials were observed optimizing the properties of the carbon matrix and facilitating the fix of atomic Ni atoms, which were demonstrated as the dominant active sites for electrocatalytic CO2 reduction. The electrocatalyst exhibited excellent performance to convert CO2 to CO with the maximal Faradaic efficiency of 97% for CO production at a low overpotential of 0.79 V and considerable CO partial current density of 27.2 mA cm-2. This work provides a novel pathway to generate metal single sites on N-rich carbon by tuning the local coordination environment of MOF precursors. In order to improve the performance of Ni@N-C catalyst for electrocatalytic CO2 reduction, in particular the long-term stability, another strategy was developed. In Chapter 4, Ni nanoclusters with an average size of 1.9 nm were evenly dispersed on N-doped carbon substrate from a bimetallic Ni/Zn-based MOF. The catalyst exhibited stable catalytic performance over 40 h with constant current density and nearly 100% selectivity for CO. By varying the ratio of Ni and Zn species in MOF precursors, the size of derived Ni particles can be controlled which was found as an important factor in tuning the electrocatalytic activity and selectivity for CO2 reduction. Density functional theory calculations revealed the advantage and mechanism of CO2 reduction on Ni nanoclusters compared with bare N-doped carbon and oversized Ni particles. In Chapter 5, single Cu sites were successfully anchored on a two-dimensional COF as co-catalysts for highly selective photocatalytic CO2 reduction under visible light. The Cu-modified COF exhibited an enhanced CO formation rate of 197 µmol g-1h−1 and a high CO selectivity of 92.5% over H2 production. The Cu-N coordination was demonstrated to facilitate visible-light harvesting and achieve faster electron transfer to active Cu sites with good charge carrier separation ability. In summary, this thesis provides contributions in the synthesis of transition metal-based catalysts derived from MOF and COF materials for promising electro- and photo-catalytic CO2 reduction. By dispersing transition metal sites on MOF-derived carbon materials and COF supports, the efficiency and selectivity of electrochemical and photochemical CO2 reduction have been greatly improved. It is expected that the material synthesis strategies and findings for optimizing catalytic performance in this thesis can provide new insights for designing more economically viable and sustainable catalysts for practical use in the future.